Substrate Warpage analysis During Solger Reflow Process - Beh, Keh Shin (2004)
Organic substrate is a composite panel consists of several materials such as BT core, copper, dielectric, solder resist and plugging material. As different material has different material property, when the organic substrate is exposed to thermal excursion in the manufacturing process, the substrate warps. In this project, both experimental and simulation study were carried out in order to have a better understanding on the substrate warpage behaviour during the solder reflow process. In the experimental analysis, substrate warpage throughout the solder reflow process was measured by using shadow moirÃ©. Besides that, the thermally induced warpage due to the temperature rise was obtained by subtracting the measured warpage from the initial warpage. Finite element analysis was performed to predict the thermally induced warpage during the solder reflow process. Both results from the experiment and simulation were compared in order to validate the finite element models. A parametric study of the impact of design parameters and material properties on substrate warpage during the solder reflow process was performed. A total of 6 parameters have been investigated including material properties, copper volume, copper distribution, plated through hole (PTH) number, PTH array and substrate thickness. The results of these analyses have produced general guidelines which can be refer when designing the substrate and also selecting the substrate materials.